Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Adsorption of chlorogenic acid in aqueous solution of Chrysanthemum morifolium (Chuju) by walnut shell-derived biochar - Ying Gao; Nan Zhang; Xinran Xu; Ruolin Zhang; Jiahang Liu; Zongyao Qian; Xuelian Wang; Yunbin Qin (Food Chemistry, 2025)

Per- and polyfluoroalkyl substances and platelet-related hematotoxicity: An integrated study of in silico, toxicological, and population evidence - Dihui Xu; Jie Xiang; Ruolin Qin; Zhijian Chen; Xiaofeng Wang; Peiwei Xu; Yitao Pan; Xinhan Zhang; Yan Wang; Ping Cheng; Yuan Chen; Dandan Xu; et al. (Journal of Hazardous Materials, 2025)

The impact of increased water hardness on pollutant toxicity in freshwater aquatic organisms - Guangchao Shi; Jiawei Wang; Jianwei Yu; Sida Qin; Ruolin Liu; Dan Wu (Environmental Monitoring and Assessment, 2025)

Design and construction of an artificial labor-division consortium for phenanthrene degradation with three-functional modules - Yiyang Liu; Ruolin Qin; Xiaoqiang Jia (Chemosphere, 2024)

Recent advances and optimization strategies for the microbial degradation of PCBs: From monocultures to microbial consortia - Rui Chen; Ruolin Qin; He Bai; Xiaoqiang Jia (Critical Reviews in Environmental Science and Technology, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Variation in the attached community structure and function of artificial habitats during ecological succession: A case study of the artificial reef area in Bailong Pearl Bay, China - Ruolin Li; Yu Guo; Ankai Zhang; Shuo Zhang; Hui Zhang; Chuanxin Qin (Frontiers in Marine Science, 2022)
With the continuous development of ports, ship transportation, resource extraction and artificial habitat deployment, an increasing number of artificial structures have created new usable spaces for marine organisms, and the biological communities living on their surfaces have undergone ecological succession. However, related studies have ignored ecological functions, interspecific relationships, and stability in different successional stages. Based on traditional taxonomy, this study applied functional diversity, niche overlap and niche breadth indexes to compare the attached organisms on artificial reefs (ARs) with different construction times in Bailong Pearl Bay, Fangchenggang City, Guangxi Zhuang Autonomous Region, China. The change trends of richness, habitat resource supply, resource utilization degree and efficiency, and interspecific relationships during the succession process were analysed. The results indicated that richness increased with functional diversity. While the number of species increased, the attached organisms showed different functional characteristics, and the number of species with identical traits decreased. The attached community in the later stage of development had a higher degree of utilization of ecological space, more comprehensive and efficient utilization of effective resources, a stronger degree of complementarity of organismal niches, and weaker interspecific competition. In the early stage of the developmental process, the attached community was affected by more environmental factors and had very significant correlations with those factors. The combination of the niche overlap index and the niche breadth index indicated that the resource supply supporting the survival and development of the attached organisms on the ARs with earlier construction times may be greater. The decrease in the number of biomarkers, the similarity of biomarkers belonging to the same family, and the similarity of dominance alternation all indicated that during the process of long-term development and community succession, the organisms attached to the various parts of the ARs tended to become more similar.

New Insight Into the Mechanism of Ecological Effects of Artificial Habitats: Elucidating the Relationship Between Protists Associated With Artificial Reefs and Adjacent Seawater - Ruolin Li; Yu Guo; Chuanxin Qin; Shuo Zhang; Dongping Ji; Hui Zhang; Jing Wang; Naiqian Zhao (Frontiers in Marine Science, 2022)
Artificial habitat deployment can restore natural habitats or supplement existing natural habitats. The effect of resource proliferation and protection is obvious. However, few reports have addressed the biological community association between artificial habitats and adjacent environments. Here, Illumina sequencing of 18S rDNA was performed, and the diversity, community structure, and co-occurrence networks of protists in different layers of artificial reefs (ARs) and adjacent seawater (WAR) were described to verify that constructing ARs in Bailong Pearl Bay improves local spatial heterogeneity and functional diversity. In terms of the degree of species interaction, the protist communities were ranked as follows: surface and bottom of WAR > ARs and WAR > different layers of ARs. The α-diversity of protists associated with ARs and WAR decreased with an increase in depth. Protist diversity was greater in WAR than in ARs. β-Diversity analysis revealed significant differences in protist community structure between WAR and ARs ( P < 0.05), and the upper layers of ARs and the middle or bottom layers of ARs differed. The key topological features of protist networks showed more positive interspecific interactions in the AR-associated protist community, a higher degree of niche differentiation, and higher complexity and stability. The keystone protists in the bottom seawater layer displayed community functions that were biased toward initial fixation in the ocean carbon cycle. The AR-associated protist community tended to participate in carbon transfer in the food chain and decomposition and utilization of dissolved organic matter (DOM). This study revealed significant differences in protist community structure between ARs and the adjacent environment, and the ecological functions of the key phyla were found to be related. In conclusion, protist communities in WAR may provide food sources for AR-associated heterotrophic protists. A variety of key phyla associated with ARs have biological roles in the carbon pump via their ecological characteristics.

Extracellular ATP promoted pollen germination and tube growth of Nicotiana tabacum through promoting K+ and Ca2+ absorption - Yansheng Wu; Baozhi Qin; Kaili Feng; Ruolin Yan; Erfang Kang; Ting Liu; Zhonglin Shang (Plant Reproduction, 2018)

Association between non-steroidal anti-inflammatory drug use and melanoma risk: a meta-analysis of 13 studies - Shan Li; Yanqiong Liu; Zhiyu Zeng; Qiliu Peng; Ruolin Li; Li Xie; Xue Qin; Jinmin Zhao (Cancer Causes & Control, 2013)